Assessing the Empowerment of Mosques with the Maqashid Sharia Index - Jajuli, M. Sulaeman; Misno, Misno; Susilawati, Erni (Equilibrium: Jurnal Ekonomi Syariah, 2023)
This study aims to assess the mosque empowerment index formula based on Maqashid Sharia. This formula serves as an instrument to measure the level of mosque empowerment in Bogor, Indonesia. It consists of six criteria based on the Maqashid Sharia, including protecting religion, life, intellect, lineage, property, and the environment. The data analysis technique employs the Analytical Network Process (ANP) in conjunction with the Super Decision 2.10 software to construct the index model structure. The results of the formula calculation in each of the three model mosques revealed significant discrepancies. The Andalusia Mosque has achieved a remarkable score of 0.96, positioning it as the top-ranking mosque in terms of its significant degree of empowerment within the local community. The following mosque is the Ar-Rahman Mosque, which has a value of 0.69 and is classified as an empowered mosque. Finally, the Al-Muhaajirin mosque has a value of 0.57, indicating that it belongs to the group of quite empowered mosques and can be given priority consideration for help in the future. Specifically, this study becomes the first comprehensive assessment of mosque empowerment in Indonesia by utilizing the Maqashid Sharia Index across three mosques.